‘Securing’ the Indian Ocean? Competing regional security constructions - Rumley, Dennis; Doyle, Timothy; Chaturvedi, S. (Routledge, 2012)
Dictated and driven to a significant extent by the changing dynamics of the knowledge–power equation, regional constructions are devised and propagated for a range of purposes – describing economic success, structuring a set of relationships, reproducing a particular vision of (in)security or organising a specific function, such as to maximise economic cooperation, to minimise insecurity or to fashion a particular form of security architecture. It is argued that there are three competing regional constructions for security (currently in circulation) in the Indian Ocean Region, emanating largely from Australia, the United States and India – an Indian Ocean-wide concept, an East Indian Ocean construct and an Indo-Pacific concept. It is suggested that there exists an overriding narrative in favour of an ‘Indo-Pacific’ construction at the expense of Indian Ocean concepts. As a result, it is concluded that the Indian Ocean Rim Association for Regional Cooperation (IOR-ARC) will remain relatively weak for the foreseeable future and that, unless there is a concerted attempt to involve China in a new maritime security regime, the discourse and practices of regional security might become the preserve of an Indo-Pacific alliance comprising Australia, India, the United States and other East Asian states, including Japan.